RANCANG BANGUN SISTEM PEMANTAU PERUBAHAN CUACA MENGGUNAKAN SENSOR GMM220 VAISALA DAN SHT30 DENGAN DATA LOGGER RASPBERRY PI - Muhammad Zia Ulhaq (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2022)
Today, climate can affect to human activity. Climate and weather are related to each other. Weather is a state of the atmosphere in a daily order or in a short period of time. Weather is only the smallest part of the effects of climate change. The parameters of both are temperature, humidity, wind and others. At this time significant changes in climate parameters will result in global warming caused by the greenhouse effect. The greenhouse effect is the trapping of gases in the atmosphere, including carbon dioxide, carbon monoxide, methane, chlorofluorocarbons, hydrofluorocarbons and others. Carbon dioxide gas is the largest in the atmosphere than other gases. The increase in carbon dioxide will increase the air temperature and reduce the humidity if it is significantly. In this final project, a tool and system will be designed that can monitor weather and climate change. By using a sensor module that can detect and measure Carbon dioxide concentration, temperature and humidity. Raspberry Pi as a data processor and data logger that can record data with measurements in real time. This research succeeded in obtaining accuracy values above 96% from each tool, recording data and displaying data on average temperature, humidity, CO2, max, min CO2 as well as color graphs of CO2.